(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Gandomkar H, Shekarabi SPH, Abdolhay HA, Nazari S, Mehrjan MS. 2020. Genetic structure of the Capoeta aculeata populations inferred from microsatellite DNA loci. Biodiversitas 21: 4565-4570. The present study aimed to investigate the genetic variation of Capoeta aculeata on the basis of DNA microsatellite loci from three rivers (Beshar, Khersan, Maroun) in Kohgiluyeh and Boyer-Ahmad Province in Iran. DNA from fin clips of 120 specimens extracted and was examined with eight microsatellite markers. Genetic differences between the populations were discerned by pairwise comparison based on allelic distribution. The average number of alleles per locus ranged from 4 to 14, while the average observed heterozygosity (Ho) at various loci varied between 0.212 to 0.579, implying that a moderate level of genetic variation. Among three populations, Maroun River population displayed the highest level of variability in terms of heterozygosity. Tests of Hardy-Weinberg showed that the microsatellite loci deviated significantly in the populations. The results indicate that some of the populations were significantly differentiated from one another based on pairwise FST estimates. Genetic distance-based measures supported the clustering of Maroun, Beshar, and Khersan rivers. The neighbor-joining dendrogram topology constructed on the basis of genetic distances among populations supported observed division between the populations. The non-significant differentiation between C. aculeata samples from Beshar and Khersan can be explained by a relative disconnection of these two populations and/or small amounts of gene flow.